Small Molecules Modulating Biogenesis or Processing of microRNAs with Therapeutic Potentials - Li, J.; Zhang, W.; Zhou, M.; Kooger, R.; Zhang, Y. (Current Medicinal Chemistry, 2013)
MicroRNAs (miRNAs) are single-stranded non-coding RNAs with the ability to regulate gene expression at post-transcriptional level. Typically, miRNAs function by binding to the 3’ untranslated regions (UTR) of target mRNAs, leading to the degradation or repressed expression of target genes. It is estimated that miRNAs are involved in almost every genetic pathway and the regulation of miRNAs plays important roles in physiological and pathological processes. Small molecules that can regulate miRNAs have great potential as probes to explore miRNAs-mediated regulatory network. Small-molecule regulators of disease-related miRNAs also hold the potential as novel therapeutic agents. Based on the screening systems developed in recent years, several small-molecule regulators have been identified as specific or universal regulators of miRNAs. Therapeutic potentials of these small molecules have also been demonstrated. A general review on the reported small molecules modulating the biogenesis or function of miRNAs will be presented in this paper, with emphasis on the screening methods, proposed mechanism of action and the therapeutic potentials of these small molecules.
Keywords: therapeutics